2021
DOI: 10.3390/cancers13236133
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Albumin-to-Alkaline Phosphatase Ratio Is a Prognostic Marker in Lung Cancer Patients: A Registry-Based Study of 7077 Lung Cancer Patients

Abstract: The albumin-to-alkaline phosphatase ratio (AAPR) is a novel promising prognostic marker in cancer patients. However, the evidence for its significance in lung cancer is scarce. Therefore, we assessed the prognostic value of the AAPR in a large cohort of lung cancer patients. Data on lung cancer patients diagnosed from January 2009 to June 2018 were extracted from the Danish Lung Cancer Registry and combined with data on the pretreatment serum AAPR level extracted from the clinical laboratory information system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The AAPR and NRI are also based on albumin, which has been verified as a prognostic factor for many cancers. 21,[38][39][40][41] In our study, low NRI and low AAPR were significantly related to poor OS. Moreover, as observed in previous studies, performance status, LDH, and age were significantly related to survival outcomes in our patients with MM.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The AAPR and NRI are also based on albumin, which has been verified as a prognostic factor for many cancers. 21,[38][39][40][41] In our study, low NRI and low AAPR were significantly related to poor OS. Moreover, as observed in previous studies, performance status, LDH, and age were significantly related to survival outcomes in our patients with MM.…”
Section: Discussionsupporting
confidence: 54%
“… 20 Fractures are also common skeletal-related events in patients with MM exhibiting extensive bone destruction, and serum ALP levels may be increased in patients with fractures. Although the albumin (Alb)–ALP ratio (AAPR) has been probed as a predictive factor in patients with various types of cancers, 21 , 22 its prognostic value for MM remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29]. However, there is limited evidence from large-scale general populations, making direct comparisons with our study challenging due to the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 76%
“…The ALP-to-ALB ratio (APAR), a novel prognostic marker amalgamating ALP and ALB, has been proposed and exhibits promising prognostic value in various cancers and other diseases [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Moreover, APAR exhibits superior predictive performance for clinical outcomes when compared with independent ALP and ALB measurements [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the potential protective effect of a higher body weight has been reported and may be attributed to the white adipose tissue involved in the host defense and inflammatory response that may increase sensitivity to anti-PD-1/PD-L1 therapies 4 , 38 . Decreased albumin is often associated with systemic inflammatory responses and reflects a poor nutritional status, while elevated alkaline phosphatase (ALP) levels are often found when cancer extends to the bone or liver 39 . Both decreased albumin and elevated ALP levels have been independently associated with cancer progression, and more recent research has demonstrated the potential role of the albumin-to-ALP ratio (AAPR) as a prognostic factor in NSCLC and small cell lung cancer, with decreasing AAPR associated with poorer survival 40 .…”
Section: Discussionmentioning
confidence: 99%